Confiabilidade de medidas de força de preensão palmar em mulheres com artrite reumatoide utilizando os dinamômetros jamar e o de bulbo - Karla Gonçalves Diogo (2017)
Introduction: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that evolves causing joint deformities, reduced overall muscle strength and functional disabilities. The prevalence varies from 0.5 to 1% in the general population and is higher in women. Objectives: (1) to measure the concurrent validity of handgrip strength measurements (HGS) of women with RA; (2) to compare HGS, functional capacity (FC) and fatigue among middleaged and elderly women; (3) to verify the association of HGS measurements with FC measurement and fatigue in the group of middle-aged and elderly women. Methods: This study consists of a methodological and cross-sectional study with a sample recruited from the Rheumatology Service of the Bias Fortes Ambulatory of the Hospital das Clínicas of the Federal University of Minas Gerais. For the evaluation of the HGS, the Jamar and Bulb pneumatic dynamometers were used. Fatigue was assessed by the Functional Assessment ofChronic Illness Therapy (FACIT-F) 4 and FC by the 4m walk test. The concurrent validity of HGS measurements was analyzed using the Bland-Altman analysis. The comparison between groups was by Student's t-test and the association analysis by means of Pearson's correlation test. The participants aged 45 to 59 years (young group - YG) were compared with those older than 60 years (elderly group - EG) in relation to HGS, FC and fatigue, and the association between the variables was analyzed. Results: 41 women (aged 45 and over) participated. The mean age was 60.63 (± 8.35) years. The Bland-Altman analysis showed that there is no agreement between the HGS measurements between the Jamar and Bulbo dynamometers (bias = 9.04, p <0.01). The comparison between YG (9.87 ± 7.32) and EG (16.29 ± 6.64) showed statistically significant difference (p = 0.01) for HGS. In the association analysis, a moderate positive correlation was observed between gait speed (GS) and FACIT-F 4 in YG (r = 0.53, p = 0.01) and in EG there was a moderate positive association between FPP and GS (r= 0, 51, p = 00.2). Other analyzes were not significant (p> 0.05). Conclusion: There was no consistency between the measurements of the two dynamometers used. Elderly women with RA had high overall muscle strength. Fatigue influenced the functional capacity in those ofmiddle age - YG, while in the elderly the functional capacity was related to muscular strength. These data pointed to the importance of assessing muscle strength in women with RA.